Chinese expert consensus on the application of intravenous immunoglobulin in hematological diseases - Guo, Zhi; Zhu, Jie; Wang, Jun; Wang, Liang; Tang, Feifei; Huang, Huiqiang; Xia, Zhongjun; Liu, Liqiong; Wang, Danyu; Zhong, Nan; Zhou, Huanhuan; Zhou, Zhaogui; et al. (Frontiers in Medicine, 2025)
Intravenous immunoglobulin (IVIG), first developed for the treatment of patients with antibody deficiencies, is now widely used in clinical practice, especially in hematological and immune system diseases, and its application in hematological oncology chemotherapy, cellular immunotherapy and hematopoietic stem cell transplantation (HSCT) is becoming more and more common. The Chinese Collaborative Group for Infection Immunology and Microecology Research Translation Collaborative Group organized relevant experts to discuss and propose the “Chinese expert consensus on the application of intravenous immunoglobulin in hematological diseases,” which was formulated based on the progress of research on the application of IVIG in blood diseases, and provides a basis for the standardization of the use of IVIG in hematologic disorders.